Pemberdayaan Strategi Pembelajaran Etnomatematika Permainan Ma'cciccu Dalam Meningkatkan Kemampuan Berpiki Analitik Matematika - Diningsih, A. Widia; Sirwanti; Andi Muhammad Irfan Taufan Asfar (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Mathematics education in Indonesia experiences various challenges, especially in improving students' analytical thinking skills. One promising approach is ethnomathematics. The ethnomathematical approach to mathematics learning is carried out by integrating mathematics with the culture or life of students. Students are expected to be able to relate mathematical concepts to their daily lives. The ethnomathematics approach avoids mathematics learning that is too formal and abstract so that mathematics learning will be easier to understand and interesting in the eyes of students. This article will discuss how empowering ethnomathematics learning strategies through Ma'cciccu games can improve students' mathematical analytical thinking skills. This implementation method uses qualitative descriptive. This method produces descriptive data in the form of written and oral sentences from people and observed behaviors, in this case SDN 59 Garotin students as the object of activity. This activity produces an overview of certain events, the description in question is the process of empowering the ethnomathematics learning strategy of the Ma'cciccu game in improving mathematical analytical thinking skills. After conducting hands-on practice on how to learn ethnomathematics strategies through the Ma'cciccu game, students' analytical thinking skills increased, which initially lacked problem solvin skills, low numeracy skills, and lack of good collaboration and communication. Empowering ethnomathematics learning strategies through Ma'cciccu games is an innovative approach in improving students' analytical thinking skills. By integrating local culture into learning, students not only learn mathematics, but also understand the relevance and application of mathematical concepts in daily life through Ma'cciccu games students can develop the necessary skills to face future challenges.